ANALYSIS OF TOURIST VILLAGE MANAGEMENT STRATEGY IN INCREASING TOURIST ATTRACTIVENESS IN LINAWAN VILLAGE, SOUTH BOLAANG MONGONDOW REGENCY (Jurnal Ilmu Manajemen dan Bisnis, 2025)
This study aims to (1) determine the management strategy for tourist villages and (2) determine the factors influencing tourist attraction. Linawan Village has marine tourism potential in the form of beautiful beaches and mangrove areas, but management is not yet optimal. The research method used a descriptive qualitative approach, with data collection techniques through observation, in-depth interviews, and documentation of informants such as Pokdarwis, village government, MSMEs, the Tourism Office, community leaders, tourists, and youth organizations. The results of the study indicate that (1) management strategies include tourism promotion, partnerships with the private sector, human resource development, mapping tourism potential, and revitalizing the tourism village acceleration team. (2) Factors influencing tourist attraction include accessibility, infrastructure, promotion and information, and price. The main obstacles are limited supporting facilities, suboptimal coordination between stakeholders, and weak digital promotion. The study recommends an integrated and community-based management strategy, utilizing digital media, strengthening partnerships, increasing human resource capacity, and developing new tourist attractions. These results are expected to serve as a reference for the management of Linawan Tourism Village and a reference for the development of sustainable tourism villages in other areas.